IMPLEMENTASI JURIMETRI DALAM PENENTUAN JUMLAH NAFKAH ANAK - Asnawi, M Natsir (Jurnal Hukum dan Peradilan, 2016)
There are some perspectives in analyzing justice as an empirical and testable concept. Jurimetrics is one of those perspectives to perform justice as a value to be measured and tested. Jurimetrics concern on analyzing legal issue based on empirical database. Jurimetrics mainly applied in some cases, such as indemnity based on unlawful act and deciding child livelihood. Jurimetrics is highly compatible for those matter notably if Judges want to established a testable and comprehensive value. Jurimetrics is applied by retrieving, processing, and analyzing quantitative database either by simple or complex mathematical approach.Keywords : jurimetrics, child livelihood, justice